2018
DOI: 10.18632/oncotarget.26145
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio as a predictive or prognostic factor for gastric cancer treated with nivolumab: a multicenter retrospective study

Abstract: IntroductionThe neutrophil-to-lymphocyte ratio (NLR) is effective as a predictive factor for lung cancer treated with nivolumab. The objective of this study was to determine the effectiveness of NLR for patients with advanced gastric cancer (AGC) treated with nivolumab.MethodsThis was a multicenter, retrospective study of patients with AGC treated with nivolumab from June 2017 to December 2017. The NLRs were calculated before the first cycle (NLRpre) and two weeks after the first administration (NLRpost).Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 23 publications
3
41
1
Order By: Relevance
“…It is consequently favorable to have more LYMs relative to neutrophils (i.e., a low NLR). Relationships between NLR and OS have been reported previously across both tumor‐types and checkpoint inhibitors . NLR provided nearly as good improvement as LYM in the AAD model (1.7 × 10 −4 vs. 1.0 × 10 −4 ; Table ) and could consequently have been exchanged to NLR with only minor worsening of the model fit.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It is consequently favorable to have more LYMs relative to neutrophils (i.e., a low NLR). Relationships between NLR and OS have been reported previously across both tumor‐types and checkpoint inhibitors . NLR provided nearly as good improvement as LYM in the AAD model (1.7 × 10 −4 vs. 1.0 × 10 −4 ; Table ) and could consequently have been exchanged to NLR with only minor worsening of the model fit.…”
Section: Discussionsupporting
confidence: 58%
“…Relationships between NLR and OS have been reported previously across both tumor-types and checkpoint inhibitors. 6,[35][36][37] NLR provided nearly as good improvement as LYM in the AAD model (1.7 × 10 −4 vs. 1.0 × 10 −4 ; Table S3) and could consequently have been exchanged to NLR with only minor worsening of the model fit. This was also confirmed in the KMMCVPC for NLR where AAD were well predicted by the models based on C2YE and C2YASOT data ( Figure S4).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients with high NLRs, patients with low NLRs are likely to have the inflammatory reaction environment mediated by lymphocytes [30]. Ogata et al [33] and Bagley et al [34] reported that the NLR might predict the tumor response of nivolumab in gastric cancer and non-small cell lung cancer, respectively. Tada et al [35] reported that ramucirumab suppresses tumor infiltration of effector regulatory T-cells (eTreg) and decreases programmed cell death protein 1 (PD-1) expression by CD8+ T-cells, subsequently enhancing antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies has indicated that a high preoperative NLR is associated with poor patient outcome in various types of cancer, including pancreatic cancer, renal cancer, non-small cell lung cancer, gastric cancer, hepatocellular carcinoma, and various other solid tumors. [ 6 , 13 16 ] Using univariate and multivariate analysis, the present study investigated the relationship between multiple clinicopathological factors and the prognosis of DCC patients. It was ultimately confirmed that a high preoperative NLR (>2.933) is an independent risk factor for the overall survival rate of patients with DCC.…”
Section: Discussionmentioning
confidence: 99%